Fat mass to fat-free mass ratio and its associations with clinical characteristics in asthma - Rugila, Diery Fernandes; Oliveira, Joice Mara; Machado, Felipe Vilaça Cavallari; Correia, Natielly Soares; Puzzi, Vitória Cavalheiro; Passos, Natália Febrini Piassi; Freitas, Patrícia Duarte; Pitta, Fabio; Carvalho, Celso Ricardo Fernandes; Furlanetto, Karina Couto (Heart & lung, 2022)
•FM/FFM is associated with different clinical outcomes (factors) in adults with asthma.•Factors are corticosteroids, medication steps, lung function and physical activity.•Those with higher FM/FFM are more likely to be in stages 4–5 and physically inactive. Fat mass to fat-free mass ratio (FM/FFM) assesses the combined effect of the balance between fat mass and fat-free mass. Aims: to evaluate the associations beetween FM/FFM and clinical outcomes in asthma and to compare clinical characteristics between individuals with higher and lower FM/FFM. 128 participants with asthma underwent anthropometric, spirometry and bioelectrical impedance assessments. Physical activity in daily life (PADL) was assessed by the Actigraph for 7 days. Daily dose of inhaled medication, steps of pharmacological treatment, Asthma Control Questionnaire, Asthma Quality of Life Questionnaire and Hospital Anxiety and Depression Scale were also assessed. Participants were classified into two groups according to the 50th percentile of reference values for FM/FFM. Individuals with higher FM/FFM (n=75) used higher daily doses of inhaled corticosteroids, had worse lung function and fewer steps/day when compared to those with lower FM/FFM (n=53) (P≤0.021). Associations were found between absolute values of FM/FFM with lung function (FEV1 and FVC [liters]): R2=0.207 and 0.364;P<0.0001), and between the categories of lower or higher FM/FFM with steps of medication treatment (Cramer's V=0.218;P=0.016) and level of PADL (Cramer's V=0.236;P=0.009). The highest FM/FFM was a determining factor of physical inactivity (OR: 3.21;95%CI:1.17–8.78) and highest steps of pharmacological treatment (OR: 8.89;95%CI:1.23–64.08). Higher FM/FFM is significantly associated with worse clinical characteristics in individuals with asthma, such as higher doses of inhaled corticosteroids, worse lung function and fewer steps/day. Moreover, higher FM/FFM is a determining factor of physical inactivity and the highest steps of pharmacological treatment for asthma.